Gestión de seguridad y salud en el trabajo de la ISO 45001 en mercados emergentes - Lizarzaburu Bolaños, Edmundo (2021)
The objective of this research document is to provide an introduction to ISO 45001, the new occupational health and safety management system. First, presenting its background, objectives, benefits and explanation of the system proposed by the standard. Likewise, a comparison with its predecessor, the OHSAS 18001 standard, is made throughout the text, since, in addition to complying with the requirements previously proposed in said and the role of senior management as leader standard, ISO 45001 emphasizes the context of the organization of the Management System. Given the growing global competitiveness and the number of accidents registered annually by the International Labor Organization (ILO), it is advisable to be informed of the updating of this management standard. As main findings it is emphasized that the ISO 45001 standard presents new objectives of continuous improvement and total quality aligned with current quality standards, with the main objective of mitigating occupational risks through strategic organizational planning that unifies hierarchical levels in the dynamics of health and safety at work.